2019
DOI: 10.1590/1414-431x20198379
|View full text |Cite
|
Sign up to set email alerts
|

The ERBB2 gene polymorphisms rs2643194, rs2934971, and rs1058808 are associated with increased risk of gastric cancer

Abstract: Gastric cancer (GC) is the third most lethal type of cancer worldwide. Single nucleotide polymorphisms (SNPs) in regulatory sites or coding regions can modify the expression of genes involved in gastric carcinogenesis, as ERBB2 , which encodes for the tyrosine-kinase receptor HER-2. The aim of this work was to analyze the association of the polymorphisms: rs2643194, rs2517951, rs2643195, rs2934971, and rs1058808 with GC, as they have not yet been analyzed in GC patients, as well as to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“… 40 Moreover, MAPK1 (c.857–3854A > C and c.119 + 21641G > A), RAF1 (c.1669-36C > T) and HRAS (c.-1115T > C) intronic variants increased GA susceptibility on the Chilean population, 45 even when they were initially reported as variables of uncertain significance in ClinVar. Similar disparities between studies were found in Mexican population, where an increased GA susceptibility was associated with the EGFR promotor region variants c.-216G > T, c.-191C > A 49 (related to augmented expression of EGFR protein), the ERBB2 intronic variants c.-18 + 1614C > T, c.-18 + 3073G > T and the missense variant c.3418C > G, 50 classified as variables of uncertain significance in ClinVar. Also, a decreased susceptibility was associated with the TGF-β promoter variant c.-509C > T which is associated with higher TGF-β plasmatic concentration.…”
Section: Germline Risk Variants Associated To Sporadic Ga In Latamsupporting
confidence: 69%
“… 40 Moreover, MAPK1 (c.857–3854A > C and c.119 + 21641G > A), RAF1 (c.1669-36C > T) and HRAS (c.-1115T > C) intronic variants increased GA susceptibility on the Chilean population, 45 even when they were initially reported as variables of uncertain significance in ClinVar. Similar disparities between studies were found in Mexican population, where an increased GA susceptibility was associated with the EGFR promotor region variants c.-216G > T, c.-191C > A 49 (related to augmented expression of EGFR protein), the ERBB2 intronic variants c.-18 + 1614C > T, c.-18 + 3073G > T and the missense variant c.3418C > G, 50 classified as variables of uncertain significance in ClinVar. Also, a decreased susceptibility was associated with the TGF-β promoter variant c.-509C > T which is associated with higher TGF-β plasmatic concentration.…”
Section: Germline Risk Variants Associated To Sporadic Ga In Latamsupporting
confidence: 69%
“…The minor allele “G” of the exonic SNP rs1058808 causes a non-synonymous Pro1170Ala mutation to the amino acid sequence of the ErbB2 protein. Based on the information from UniProt [33], the Pro1170Ala mutation is located in the disordered region of the cytoplasmic domain of ErbB2 and was predicted to be a damaging variant with potential effects on its protein structure and function [41]. In our work, the Pro1170Ala mutation results in a marked decrease in the phosphorylation level of tyrosine residues in the ErbB2 protein, at the same time also correlates with reduced asthma risk in our study population.…”
Section: Discussionmentioning
confidence: 60%